Appendix A1: Yeast Nomenclature Systematic Open Reading Frame (ORF) and Other Genetic Designations (Alternative pre‐mRNA Splicing, 2012)
This appendix contains sections titled: Protein‐Coding Genes Recombinant Derivatives Proteins Noncoding Genes, Genes Not Encoded by Nuclear Chromosomal DNA, and other Chromosomal Features Yeast Strains References